A portable high-density absolute-measure NIRS imager for detecting prefrontal lobe activity under fatigue driving. (March 2018) - Zhao, Yue; Xu, Guoyi; Sun, Yunlong; Pan, Boan; Li, Ting
Abstract: Driving fatigue is one of the primary causes of traffic accidents nowadays. It is thus imperative to develop a technique to monitor levels of driving fatigue. The emergent near-infrared spectroscopy (NIRS) is now capable of measuring functional cerebral activities noninvasively and sensitively in terms of hemodynamic responses, shedding light on the possibility to detect signals regarding fatigue-specified cerebral activities. This work innovatively developed a NIRS device aimed at fatigue detection of drivers, and the device was designed to be portable so that it can be easily operated during driving. Moreover, the device is absolute-measure so that the data can be compared among drivers. The probe is high-density and we can visualize brain functional responses after imaging. The high sensitivity, stability, and reliabilities of our device were fully tested in the order of ink experiment, cuff experiment, and on-human test. For the in-situation on-human test, we recruited 3 taxi drivers and collected data by our device during 8 h' driving. It's found that the hemodynamics-represented cerebral activation decreased with driving duration, which indicated our device's strong potential in monitoring fatigue. Highlights: Innovatively developed a portable high-density absolute-measure NIRS imager. High effectiveness in detecting oxygenation in human blood and capability of imaging prefrontal lobe activity. A series of experiments conducted to verify the sensitivity, stability and reliability of this device.